Binding of Dumbbell Oligonucleotides to MoMuLV Reverse Transcriptase: Inhibitory Properties of RNase H Activity - Ajay Kumar (E-Journal of Chemistry)
Dumbbell oligonucleotides with loops of various chemistry were synthesized. Incubation of dumbbell oligonucleotides containing phosphorothioate bonds or trimethylene phosphate linkages in loops with S1 nuclease did not result in significant cleavage under conditions which led to the degradation of dumbbell oligonucleotide containing phophodiester bonds in the loops. The binding of reverse transcriptase of Moloney Murine Leukemia Virus (MoMuLV) was evaluated with all the five oligonucleotides. The protein binds to all the dumbbell oligonucleotides with similar affinity. The dissociation constants evaluated using PAGE band mobility shift assays were of the order of 10-7. The inhibitory properties of the retroviral RNase H activity was evaluated using 3H –UTP-labeled RNA:RNA-DNA hybrid. It was found that the best dumbbell oligonucleotide, inhibitor contained phosphorothioate residues in both the loops. Our value studies demonstrated that this particularly designed oligonucleotide displays an IC50 of 18 nM in its inhibition on the reverse transcriptase RNase H activity, a magnitude lower than that of first nucleotide reverse transcriptase of HIV-1, tenofovir, introduced by Gilead Science in the market.